Signal to noise ratio as a guideline to obtain valid auditory brainstem response results - Dzulkarnain, Ahmad Aidil Arafat (Malaysian National Society of Audiologist MANSA), 2020)
Auditory brainstem response (ABR) is regards as one of the important tests to assess the auditory brainstem function and to estimate hearing thresholds. Whilst ABR is considered objective from the patient point of view, the interpretation of the ABR requires substantial knowledge from the perspective of an audiologist. The whole processes of ABR interpretations are complex. The first important aspect in interpreting the ABR finding is to identify whether an ABR is present or absent.